Poor sleep quality in patients with multiple sclerosis: gender differences. Issue 11 (20th September 2016) - Vitkova, Marianna; Rosenberger, Jaroslav; Gdovinova, Zuzana; Szilasiova, Jarmila; Mikula, Pavol; Groothoff, Johan W.; Reijneveld, Sijmen A.; van Dijk, Jitse P.
Abstract: Objectives: Most of the psychological and physical factors associated with poor sleep quality in patients with multiple sclerosis (MS) have a different prevalence in women and men, but whether or not these factors contribute differently to sleep quality in women and men with MS remains unclear. The aim of this study was to identify possible gender differences in factors related to poor sleep quality in MS patients. Material and Methods: We collected data from 153 patients with MS. Patients filled out the Pittsburgh Sleep Quality Index (PSQI), the Hospital Anxiety and Depression Scale, and one item of the Short Form‐36 regarding pain. Results: The best model of predictors of poor sleep quality consisting of gender, depression, anxiety, pain, and the interaction between gender and pain showed that the only variable interacting with gender, which was significantly associated with poor sleep quality was pain (odds ratio [OR] for interaction of pain with male gender was 15.4, 95% CI: 2.4; 39.5). Separate models for men and women consisting of pain, depression, anxiety, after adjustment for age, disease duration, and disability showed that pain was the only variable associated with poor sleep quality in men (OR = 12.7, 95% CI: 1.9; 29.6), whereas depression (OR = 4.1, 95% CI: 1.3; 13.2) and anxiety (OR = 6.8, 95% CI: 2.4; 19.1) were in women. Conclusions: Factors contributing to poor sleep quality in MS patients differ by gender. Depression and anxiety are associated with poor sleep quality in women, whereas pain is in men. This highlights the need to apply gender‐specific approaches to the treatment of sleep disorders. Abstract : Our study explored possible gender differences in factors related to poor sleep quality in patients with MS multiple sclerosis. We found that depression and anxiety contributed to poor sleep quality in women, but pain did so in men. Our findings highlight the need to apply gender‐specific approaches to the treatment of sleep disorders.